2020
DOI: 10.1007/s00421-020-04418-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term athletic training does not alter age-associated reductions of left-ventricular mid-diastolic lengthening or expansion at rest

Abstract: Purpose The interaction of ageing and exercise training status on left-ventricular (LV) peak strain is unclear. Additionally, strain analysis across the entire cardiac cycle facilitates a more detailed assessment of deformation, yet this has not been implemented to characterize the ageing LV and in association with training status. This study investigated healthy ageing and training status on LV systolic and diastolic strain utilizing novel echocardiographic applications. Methods Forty healthy males were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Outcomes of this study agreed with Smart et al who found that measures of echocardiography (stroke volume and ejection fraction) were ultimately not altered after aerobic exercise in the form of cycling, although functional capacity improvements (Alexander et al, 2020;Smart et al, 2012). (Kitzman et al, 2010).…”
Section: Ejection Fractionsupporting
confidence: 90%
“…Outcomes of this study agreed with Smart et al who found that measures of echocardiography (stroke volume and ejection fraction) were ultimately not altered after aerobic exercise in the form of cycling, although functional capacity improvements (Alexander et al, 2020;Smart et al, 2012). (Kitzman et al, 2010).…”
Section: Ejection Fractionsupporting
confidence: 90%
“…One characteristic of advancing age is a reduced peak oxygen uptake (VO2peak) (Astrand, 1960;Beaumont et al, 2020;Dill et al, 1967;Rogers et al, 1990). This decrease accelerates with age (Hawkins and Wiswell, 2003) such that there is a ~16% decrease across the fifth decade but a ~26% decrease during the seventh decade and above (Fleg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%